The impact of Sino-foreign cooperative universities in China on Chinese postgraduate students’ learning performances in the United Kingdom and United States - Zou, Bin; Wang, Xueying; Yu, Chunmin (Frontiers in Psychology, 2022)
Sino-foreign cooperative universities in China provide English-Medium instruction (EMI) and enable students to have an international education mode. In contrast, Double First-Class universities provide non-EMI education mode in China. After graduation from their undergraduate studies in China, many students go to the USA or the UK for their postgraduate studies. However, very few studies have discussed the impact of the EMI context in Sino-foreign cooperative universities and compared students learning experience in the EMI context with the non-EMI context in China. Therefore, this study aimed to explore students’ perceptions of their learning experience from the two contexts and their impact on their postgraduate study in British and American universities. A combination of quantitative and qualitative research methods including questionnaires and interviews was adopted in this study. The findings show that students’ learning experience in the EMI context seems to benefit more than students who are from non-EMI context when they strived for their postgraduate studies in British and American universities.